Plan estratégico para el posicionamiento de una tienda de retail en Guayaquil - Mayo Hanna, Nadia Katiuska (2009)
The present work develops a marketing plan, which by means a technical qualitative named Focus Group, seeks implement improvements in one of the Branches as way for in order that it comes back to registering profitability for the Company to which it belongs, as last effort to avoid cessation of activities of the same one. For this end, we have realized a study of marketing, where we determine, that the place needs more space and variety in clothes, then to penetrate into the Technical Study, to continue with the pertinent evaluation to the Financial Study. To conclude how result, that is not suitable invest in the marketing plan because, due to the fact we don’t obtain a Better profitability, since so the business with the extension will use more own resources that without it.